Determination of urban land value: A systematic literature review - Peng Zhou; Yue Gai; Chaowei Wang (Cardiff University, Cardiff Business School, 2025)
We apply the Systematic Literature Review (SLR) approach to surveying empirical studies on urban land value. We show that research attention is directed by market size and data availability towards developed economies and residential land. Two distinct patterns of literature evolution emerge, which can be explained by methodological homogeneity adopted in the literature. Following these observations, we compare different types of methods and compile an extensive catalog of databases for land value research. Drawing from 644 factors in the empirical literature, we conduct a thematic analysis to establish a hierarchical understanding of how urban land value is determined.
Keywords: 330; Land Value; Systematic Literature Review; Thematic Analysis